The reports : decisions of the Supreme Court of Newfoundland. - Newfoundland. Supreme Court. (St. John's, N.F. : J.W. Withers, King's Printer, 1901)
Publisher varies. Vols. retrospectively numbered. Mode of access: Internet. The publication of the 1947-1949 reports leaves only the decisions of the Supreme Court for the balance of Jan.-Mar. 1949 unpublished; for 1949-1967/68 a limited number of judgements of this court were published in the Maritime Provinces report.